KEBIJAKAN PERCEPATAN PENANGANAN COVID-19 DI KOTA BINJAI BERDASARKAN PERATURAN WALIKOTA BINJAI NOMOR 16 TAHUN 2020 TENTANG KARANTINA DALAM RANGKA PERCEPATAN PENANGANAN CORONA VIRUSES DISEASES 2019 (COVID-19) DI KOTA BINJAI - Catur Suharto, Ratno Mulyadi; Marzuki, Marzuki; Affan, Ibnu (LPPM YPITI, 2021)
The spread of Corona Virus Disease 2019 (Covid-19) in Binjai City has increased which has an impact on the economy, social, security and welfare of the people in Binjai City. The formulation of the problem in this thesis is how the policy setting for the acceleration of handling Covid-19 in the city of Binjai is based on the Binjai Mayor Regulation Number 16 of 2020 concerning Quarantine in the Context of Accelerating the Handling of Covid-19, how is the implementation of the Regulation of the Mayor of Binjai Number 16 of 2020 concerning Quarantine in the context of implementing policies acceleration of the handling of Covid-19 in Binjai City, how to protect social and economic rights of the community related to the implementation of policies to accelerate the handling of Covid-19 in Binjai City. This type of research is normative juridical, namely research based on legislation and empirical juridical, namely by conducting interviews with staff/employees of the Social Service of Binjai City. Data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. The results show that the policy setting for the acceleration of handling COVID-19 in the city of Binjai is based on the Regulation of the Mayor of Binjai Number 16 of 2020 concerning Quarantine in the Context of Accelerating the Handling of Covid-19 is to suppress and decide the spread of Covid-19 in the City of Binjai and the purpose of the establishment of this Mayor Regulation is as a guideline for implementing health quarantine in the context of accelerating the handling of COVID-19 in the Binjai City area. The implementation of the Binjai Mayor's Regulation Number 16 of 2020 concerning Quarantine in the context of implementing the policy to accelerate the handling of Covid-19 in Binjai City is much less effective because people feel that they have not received legal protection. The protection of social and economic rights of the community related to the implementation of the policy to accelerate the handling of Covid-19 in Binjai City is that the Binjai City government is responsible for order, security, comfort and welfare of the community.